4c-6-(c+7)=

Simple and best practice solution for 4c-6-(c+7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4c-6-(c+7)= equation:


Simplifying
4c + -6 + -1(c + 7) = 0

Reorder the terms:
4c + -6 + -1(7 + c) = 0
4c + -6 + (7 * -1 + c * -1) = 0
4c + -6 + (-7 + -1c) = 0

Reorder the terms:
-6 + -7 + 4c + -1c = 0

Combine like terms: -6 + -7 = -13
-13 + 4c + -1c = 0

Combine like terms: 4c + -1c = 3c
-13 + 3c = 0

Solving
-13 + 3c = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '13' to each side of the equation.
-13 + 13 + 3c = 0 + 13

Combine like terms: -13 + 13 = 0
0 + 3c = 0 + 13
3c = 0 + 13

Combine like terms: 0 + 13 = 13
3c = 13

Divide each side by '3'.
c = 4.333333333

Simplifying
c = 4.333333333

See similar equations:

| 11z+5=2(4z-5) | | 5-4.9a=39.2 | | 3w^2+16w=864 | | 27-5x=-44-9x | | 20=5w-w | | 277+96+277(0.01083032491+-1y)+277y=376 | | 54=2x+4x | | 3(4-2x)=-9 | | Cos(3.1416/6) | | W(20)=13.2x+443 | | 4r-7+6r=19 | | 17=8t-36 | | Y=2x^2+12x-91 | | 7y=5-12 | | 3x^2+16-5=0 | | x/4-1/6≤12 | | -12=.2/f | | 277+96+277x+277y=376 | | 4xy-5x+4y^3=-40 | | 4(5x-4(5x+y))= | | Y=2.3x+0.2 | | 171=3x+2x^2 | | -21-18y+y=13 | | e^4x+2e^2x-24=0 | | 1000*q=1.4597 | | log81^1/9=x | | 3*-7-6y+y=13 | | 12p-15+6p=-27 | | 18x=x+y | | 0=-2x^2-10x | | Y=-0.3x-5.3 | | 2x^2+2x+25=289 |

Equations solver categories